2017
DOI: 10.5811/westjem.2017.5.33198
|View full text |Cite
|
Sign up to set email alerts
|

Availability and Accuracy of EMS Information about Chronic Health and Medications in Cardiac Arrest

Abstract: IntroductionField information available to emergency medical services (EMS) about a patient’s chronic health conditions or medication therapies could help direct patient care or be used to investigate outcome disparities. However, little is known about the field availability or accuracy of information of chronic health conditions or chronic medication treatments in emergent circumstances, especially when the patient cannot serve as an information resource. We evaluated the prehospital availability and accuracy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Nonetheless, EMS ascertainment of comorbidity appears to be a meaningful strategy to assess health status. 17 , 18 The study evaluated EMS involvement with confirmed COVID-19 cases. There may be EMS encounters in which a patient had COVID-19 but was not tested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, EMS ascertainment of comorbidity appears to be a meaningful strategy to assess health status. 17 , 18 The study evaluated EMS involvement with confirmed COVID-19 cases. There may be EMS encounters in which a patient had COVID-19 but was not tested.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the prevalence of chronic health conditions documented by EMS is likely an underestimate, and the comorbidities overall are likely even more prevalent. Nonetheless, EMS ascertainment of comorbidity appears to be a meaningful strategy to assess health status . The study evaluated EMS involvement with confirmed COVID-19 cases.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover the accuracy of this methodology has been validated when compared with hospital-sourced information. 19 The current study evaluates cumulative comorbidity as measured by the Charlson Index and does not investigate a specific comorbidity, its influence on outcome, or whether this relationship may be mediated by primary cardiac mechanism as measured by the AMSA waveform.…”
Section: Discussionmentioning
confidence: 99%
“…Information about pre-existing, clinically-recognized chronic health conditions was collected from the EMS reports 19 . Information from EMS records is available for all treated patients and has a fair to good kappa with hospital-based information.…”
Section: Data Collection and Definitionsmentioning
confidence: 99%
“…Focusing on the content and design of health websites, some quality principles have been applied in a large number of studies. For example, researchers attempted to evaluate the content of health information from the principle such as accuracy (Buhi et al, 2010;Foster,Florea, Fahrenbruch, Blackwood, & Rea, 2017), completeness (Dutta-Bergman, 2004;Alwhaibi et al, 2019), currency (Williams, 2003), credibility (Avery, 2010;Ma & Atkin, 2017), and readability (Chi, Jabbour, & Aaronson, 2017;Lam, Roter, & Cohen, 2013). Website design was usually evaluated by principles of accessibility (Rezniczek et al, 2015), esthetics (Weymann, Härter, & Dirmaier, 2014), and interactivity (Klila et al, 2013).…”
Section: Principles Instruments and Methods Of The Quality Evaluatimentioning
confidence: 99%